Research on the Legal System of Copyright Protection of We Media Platforms - Chunyu Song; Ming-Hsun Hsieh (RES MILITARIS, 2023)
With the development of we media, the global knowledge system and communication platform can be connected with each other under the support of Web2.0 technology, and any general public can "speak up" in public through we media platforms. This social phenomenon that everyone can be a "publisher" has caused many copyright infringement risks and disputes. The reason lies in the bias of interests in China’s judicial identification standards for the infringement liability of we media platforms and the defects of system design for the copyright clauses of we media platforms in legislation. In this study, we believe that the optimization of legal regulation of copyright on China’s we media platforms needs to start from the evolution of network copyright protection rules. We should systematically analyze the judicial decision rules of copyright on we media platforms, and propose optimization strategies through the causes. China’s copyright protection of we media platforms should conform to technological development, require we media platforms to bear more copyright protection responsibilities, and effectively reconstruct the duty of we media platforms in legislation. It will not only help solve many copyright protection problems caused by we media platforms, but also promote the sound operation of China’s we media platforms, and safeguard the legitimate rights and interests of copyright owners.